Development and characterization of flax/carbon/Kevlar reinforced bio-phenolic/epoxy blends hybrid composites for ballistic helmet - Ismail, Ahmad Safwan (2023)
Nowadays, the needs of high-performance materials have led the researcher to study various method in producing new material through modification or synthesis of polymers. Polymer blends is one of the methods in polymer modification which can be used to improve the overall performance of polymer. The first stage of this study is to investigate the effect of different bio-phenolic loading, which is 5(P-5), 10(P-10), 15(P-15), 20(P-20) and 25(P-25) wt% on the physical, structural, mechanical, morphological, dynamic mechanical and thermal properties of epoxy matrix. The polymer blends have a void content of less than 5% and water absorption of less than 1%. P-20 showed the highest tensile strength, flexural strength and impact resistance while P-25 showed the highest tensile and flexural modulus. The addition of bio-phenolic to epoxy matrix has improve the dynamic mechanical analysis (DMA) and thermal stability of polymer blends. Based on the analysis it was revealed that polymer blend with 20wt% bio-phenolic show optimum formulation. This formulation will be used in second and third stage of this study. The second stage of the study was designed to evaluate the physical, mechanical, morphological, dynamic mechanical and thermal properties of bio-phenolic/epoxy polymer blends with incorporation of flax fabric as reinforcement. Flax reinforced bio-phenolic/epoxy composites was fabricated with different fibre loading, which is 30(F-30), 40(F-40) and 50(F-50) wt%. The obtained results showed that addition of flax fabric has increase the water absorption and density of the composites while the void content of the composite was reported less than 3%. F-50 showed the highest tensile properties and impact strength while F-40 has the highest flexural properties. The addition of flax fabric improved the DMA of the composite but decreased its thermal stability. The analysis reveals the optimum fibre loading is 50wt% and it will be used in the third stage of the study. Flax/carbon/Kevlar reinforced biophenolic/ epoxy hybrid composites were fabricated with different ratio of Flax fabric and carbon/Kevlar fabric (F/CK) which is 100/0 (F), 75/25/ (75F25CK), 50/50 (50F50CK). 25/75 (25F75CK) and 0/100 (CK). The hybrid composites were analysed based on physical, mechanical, morphological, dynamic mechanical, high velocity impact and thermal properties. The density of the composite increase while water absorption decreases with addition of carbon/Kevlar fabrics. The void content of the composite was reported to be less than 2%. The hybrid composite, 25F75CK have tensile and flexural strengths that are about 70% and 82%, respectively, of those of the CK composites. In addition, tensile modulus, flexural modulus and impact strength of hybrid composite, 25F75CK is better compared to CK composite. Moreover, the DMA and thermal stability of the composite increase with addition of carbon/Kevlar fabrics. In addition, the high velocity impact test of hybrid composite 25F75CK showed there is no significant different in energy absorption and ballistic limit compared to carbon/Kevlar composite where the different is 5.50% and 2.79%, respectively. The study found that the hybrid composite 25F75CK has the best overall mechanical properties and comparable ballistic properties to carbon/Kevlar composites. This suggests that 25F75CK hybrid composites have potential for use in ballistic helmet applications.